Damage zone propagation and support pressure estimation around two access tunnels of the Barapukuria coalmine in Bangladesh: a two-dimensional numerical modeling approach - Islam, Md. Rafiqul; Omar Faruque, Mohammed; Shinjo, Ryuichi (International Journal of Advanced Geosciences, 2015)
The present study uses a two-dimensional boundary element method (BEM) numerical analysis to predict damage zone propagation associated with the required support pressure estimation around the two access tunnels of Barapukuria coalmine in northwest Bangladesh. Two tunnels at different depths are presented here. The stability of the two tunnels that was driven through the weak rocks’ strata of Gondwana formation is examined at depths below the surface 290 m and 453 m. The two tunnels involve horseshoe-shaped design. The shallower tunnels, which are located below the surface 290 m, are presented by model A. The deeper tunnels, which are located below the surface 453 m, are presented by model B. Both tunnels are horseshoe-shaped with a height and span of about 4.5 m and 4 m, respectively. The modeling analysis was carried out in two stages to predict the damage zone and required support pressure. The first stage considered the model without support installation. The second stage measured the model with non-uniform internal support pressure installation. It is reasonable to mention that prior and subsequent to the support pressure estimation, three important parameters, like- strength factor, failure trajectories, and deformation boundaries in the vicinity of the two tunnels have been computed properly. Final results reveal that the strength factor values ranged from 0.33 to 0.99 would create the intense deformation at the roof and sidewalls. The damage zone would be extended from 0.64 to 0.74 m towards the roof and sidewalls. The damage zone would be ranged from 1.95 to 2.21 m, for shallower and deeper tunnels, respectively. For shallower tunnels, the required support pressure would be ranged from 4.0 to 9.0 MPa. For deeper tunnels, the essential support pressure would be ranged from 7.0 to 14 MPa.